Method for directionally removing impurity elements of pegmatite type high-purity quartz

Through a pegmatite-type high-purity quartz impurity element directional removal method including crushing, ore washing, grinding grade, reselection, flotation, constant temperature micro-pressure leaching, roasting-water quenching, ultrasonic leaching and high-temperature heat treatment, the problems of low yield and low impurity removal rate of existing high-purity quartz purification processes are solved, and efficient purification of high-purity quartz and the production of high-purity products are achieved.

CN119569068AActive Publication Date: 2025-03-07ZHENGZHOU MINERALS COMPOSITIVE UTILIZATION RES INST CHINESE GEOLOGICAL ACAD

Patent Information

Application Number
CN202411753221.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing high-purity quartz purification process has low yield and low impurity removal rate, making it difficult to achieve high-purity quartz sand products with SiO2≥99.998%.

Method used

A method of directional removal of pegmatite-type high-purity quartz impurity elements, including crushing, ore washing, grinding grade, reselecting, flotation, constant temperature micro-pressure leaching, roasting-water quenching, ultrasonic leaching and high-temperature heat treatment, is adopted to remove impurity elements in a directional manner through specific acid ratios and process flows.

Benefits of technology

It has achieved efficient purification of high-purity quartz, high yield, quartz purity reaches SiO2≥99.998%, and is simple in process and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569068A_ABST
    Figure CN119569068A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of high-purity quartz, and relates to a method for directionally removing impurity elements of pegmatite type high-purity quartz, which comprises the following steps: (1) crushing raw materials by a crusher, washing ore, grinding and grading, reselecting and floating to obtain quartz concentrate; (2) adding the quartz sand into the leachate A for constant-temperature micro-pressure leaching, and washing to obtain primary quartz sand; the leachate A is mixed acid of HF, HCl and HNO3, the concentration ratio of the HCl to the HNO3 is (3-12): 1, the concentration ratio of the HCl + HNO3 to the HF is smaller than or equal to 3, and the sum of the concentrations of the HCl, the HCl and the HNO3 is larger than or equal to 3 mol / L; (3) roasting and water quenching to obtain intermediate quartz sand; (4) adding the quartz sand into the leachate B for ultrasonic leaching, washing, and carrying out high-temperature heat treatment to obtain high-purity quartz sand; the leachate B is a mixed acid of HF and HCl, HF is 0.5-2 mol / L, and the concentration ratio of HCl to HF is less than or equal to 3. According to the method, the 4N8-grade high-purity quartz sand can be obtained, the yield is high, the process is simple, and operation is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-purity quartz preparation, and in particular relates to a method for directional removal of impurity elements in pegmatite-type high-purity quartz. Background Art

[0002] The unique molecular chain structure, lattice shape and lattice change law of high-purity quartz give it excellent chemical stability, extremely low volume expansion coefficient, high temperature resistance, high insulation and voltage resistance, low and stable ultrasonic delay performance, mechanical properties higher than ordinary glass, ultraviolet spectrum transmission performance, visible light and near-infrared spectrum transmission performance. It occupies a pivotal position in the fields of semiconductors, photovoltaics, optical fibers, electric light sources, etc., and is an indispensable raw material for strategic high-tech industries.

[0003] There are few deposits in the world that can process high-purity quartz. The main deposit types are granite pegmatite, vein quartz, quartzite, etc. 90% of the world's high-end high-purity quartz raw materials come from the granite pegmatite deposit in Spruce Pine, North Carolina, USA. In view of the existing successful cases and the advantages of large scale, low fluid inclusion content and stable ore quality, pegmatite high-purity quartz resources are currently considered to be the most important source of high-purity quartz raw materials in the world.

[0004] Impurities in pegmatite-type high-purity quartz resources mainly include three types: mineral impurities, inclusion impurities, and lattice impurities. High-end high-purity quartz has extremely high requirements for quartz purity. Not only the total amount of impurities is strictly regulated, but also key impurities such as Al, Na, and K are strictly regulated. How to remove impurities to the maximum extent has become the key to purifying high-purity quartz. Traditional purification processes are mainly prepared according to methods such as coarse crushing, calcination and water quenching, grinding and sand making, magnetic separation, flotation, and acid leaching. However, pegmatite-type high-purity quartz contains a large amount of feldspar, mica and other gangue minerals. Calcination and water quenching before grinding and sand making will cause impurity elements such as K, Na, and Ca to enter the lattice or quartz gap at high temperature, increasing the difficulty of removal. Leaching is a crucial link in the purification of high-purity quartz. Most existing processes believe that the higher the acid concentration, the better, ignoring the ratio research between various acids, resulting in low yield and low quartz purity. It is urgent to develop a directional removal technology for impurity elements in pegmatite-type high-purity quartz to improve product purity. Summary of the invention

[0005] The purpose of this application is to propose a method for directional removal of impurity elements in pegmatite-type high-purity quartz. The method has excellent purification effect and effectively solves the problems of low yield and low impurity removal rate in the existing high-purity quartz purification process. It can achieve directional removal of key impurity elements and obtain high-purity quartz sand products with SiO2≥99.998%.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for directional removal of impurity elements in pegmatite-type high-purity quartz comprises the following steps:

[0008] (1) After the pegmatite-type high-purity quartz raw material is crushed by a crusher, it is washed, ground and classified to obtain quartz sand raw material of a certain particle size, and then re-selected and flotated to obtain quartz concentrate;

[0009] (2) adding the quartz concentrate to a leaching solution A for constant temperature micro-pressure leaching, and obtaining primary quartz sand after washing; the leaching solution A is a mixed acid of HF, HCl and HNO3, wherein the concentration of HF is 1 mol / L to 6 mol / L, the concentration ratio of HCl to HNO3 is 3:1 to 12:1, the concentration ratio of (HCl+HNO3) to HF is ≤3, and the sum of the concentrations of HF, HCl and HNO3 is ≥3 mol / L;

[0010] (3) roasting and water quenching the primary quartz sand to obtain intermediate quartz sand;

[0011] (4) adding the intermediate quartz sand into the leaching solution B for ultrasonic leaching, washing and then performing high-temperature heat treatment to finally obtain high-purity quartz sand; the leaching solution B is a mixed acid of HF and HCl, wherein the concentration of HF is 0.5 to 2 mol / L, and the concentration ratio of HCl to HF is ≤3.

[0012] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred implementation, in step (1), the pegmatite-type high-purity quartz raw material is directly crushed without any high-temperature heat treatment.

[0013] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred embodiment, in step (1), quartz sand raw material with a particle size of -60 mesh to +180 mesh is obtained by grinding and classification.

[0014] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred embodiment, in step (2), the leaching temperature is 50°C to 160°C, the leaching time is ≥4h, and the liquid-solid ratio is 1:1 to 3:1.

[0015] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred embodiment, in step (2), the washing includes: first repeatedly washing with high-purity water until the pH is neutral; and then ultrasonic washing with an ethanol solution.

[0016] In the above-mentioned method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred embodiment, in step (2), in the ultrasonic washing, the ultrasonic power is 1000W to 1200W, the mass concentration of the ethanol solution is 10-30%, the liquid-solid ratio is ≥1, and the liquid-solid ratio is more preferably 10:1 to 3:1.

[0017] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred embodiment, in step (2), the washing includes: first washing with high-purity water for 5 to 10 times, and then ultrasonically washing with ethanol solution for 2 to 3 times.

[0018] In the above-mentioned method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred embodiment, in step (3), the primary quartz sand is subjected to chlorination roasting in a tubular furnace, and then immediately water quenched, and the intermediate quartz sand is obtained after centrifugal dehydration; more preferably, the roasting temperature is 600°C to 1150°C, the roasting gas is Cl2 and / or HCl, and the roasting time is ≥6h; further preferably, the water quenching is water quenching at room temperature using high-purity water.

[0019] In the above-mentioned method for directional removal of impurity elements in pegmatite-type high-purity quartz, as a preferred implementation mode, in step (4), the ultrasonic leaching time is 1h to 3h, the temperature is room temperature, the ultrasonic power is 1000W to 1200W, and the liquid-solid ratio is 1:1 to 5:1.

[0020] In the above method for directional removal of impurity elements from pegmatite-type high-purity quartz, as a preferred embodiment, in step (4), the temperature of the high-temperature heat treatment is 1100° C. to 1200° C., and the time is 0.5 h to 5 h.

[0021] Compared with the prior art, the solution of this application has the following beneficial effects:

[0022] (1) Compared with the traditional process, the process method adopted by the present invention does not perform calcination and water quenching before grinding, thereby preventing impurity elements such as K, Na, and Ca from entering the lattice or quartz gap at high temperature, thereby improving the purity of the high-purity quartz product finally obtained.

[0023] (2) The inventors have conducted a detailed study on the ratio of various acids in the leaching stage and found that with the increase of HF concentration, the loss rate of quartz itself will increase, and when it reaches a certain critical point, it will increase rapidly. And with the increase of acid concentration, the purity of high-purity quartz products will show a downward trend after reaching a certain level. And H + The concentration will affect the ionization of HF. + When the ratio of concentration to HF concentration is too high, HF2 -The formation of quartz crystals weakens the dissolution effect and reduces the purity of high-purity quartz products. The leaching agent A used in the method of the present invention can effectively remove mineral conjoined impurities and some inclusion impurities, and remove impurity elements to a great extent while ensuring the yield.

[0024] (3) The method of the present invention combines the calcination-water quenching and chlorination roasting processes. The chlorination roasting-water quenching process can effectively open the inclusions while removing impurities.

[0025] (4) The leaching agent B used in the method of the present invention mainly removes the inclusions opened by the chlorination roasting-water quenching process, and uses ultrasound to bring the leaching agent B into contact with the impurities along the cracks, thereby effectively removing the impurity elements. The impurity content at this stage is not high, and the acid ratio of the leaching agent B can effectively increase the yield of high-purity quartz.

[0026] (5) The process method adopted by the present invention as a whole fully considers the impurity removal rate, the yield of high-purity quartz and the energy consumption issues, and utilizes the characteristics of different impurities to selectively dissolve the impurity elements, with excellent purification effect, and can obtain a high-purity quartz sand product with SiO2 ≥ 99.998%, with high yield, simple process method, and easy operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 A process flow chart of a preferred embodiment of a method for directional removal of impurity elements in pegmatite-type high-purity quartz provided by the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below with reference to the accompanying drawings. Figure 1 As shown, a preferred embodiment of a method for directional removal of impurity elements in pegmatite-type high-purity quartz provided by the present invention comprises the following steps:

[0030] (1) After the pegmatite-type high-purity quartz raw material is crushed by a crusher (such as a jaw crusher), it is washed, ground and classified to obtain quartz sand raw materials of a certain particle size, and then re-selected and flotated to obtain quartz concentrate;

[0031] (2) adding the quartz concentrate into the leaching solution A to carry out constant temperature and micro-pressure leaching, and obtaining primary quartz sand after washing;

[0032] (3) calcining the primary quartz sand at a certain temperature and then quenching it with water to obtain intermediate quartz sand;

[0033] (4) The intermediate quartz sand is added to the leaching solution B for ultrasonic leaching, and after washing, it is subjected to high-temperature heat treatment (baking sand) to finally obtain high-purity quartz sand.

[0034] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, in step (1), the pegmatite-type high-purity quartz raw material is crushed by a crusher (such as a jaw crusher), washed to remove surface impurities, then ground and classified to obtain quartz sand raw material of a certain particle size, then the quartz sand raw material is re-selected to remove heavy minerals and light minerals, and then flotation is performed to remove monomer-dissociated feldspar and mica to obtain quartz concentrate.

[0035] Preferably, in step (1), the pegmatite-type high-purity quartz raw material is directly crushed without any high-temperature heat treatment before grinding. In other words, compared with the traditional process, the method of the present application does not perform calcination and water quenching before grinding, thereby preventing impurity elements such as K, Na, and Ca from entering the lattice or quartz gap at high temperature, thereby improving the purity of the high-purity quartz product finally obtained.

[0036] Preferably, in step (1), the quartz sand raw material with a particle size of -60 mesh to +180 mesh (i.e., above 180 mesh sieve and below 60 mesh sieve) is obtained by grinding and classification.

[0037] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, in step (2), first add the quartz concentrate to the leaching solution A, and perform constant temperature micro-pressure leaching in a closed container; then wash repeatedly with high-purity water until the pH is neutral; then use ethanol solution for ultrasonic washing to remove organic matter remaining on the surface of the quartz; finally centrifugal dehydration to obtain primary quartz sand. The constant temperature micro-pressure leaching is carried out in a closed container, wherein the saturated vapor pressure increases with the increase of temperature, for example, 0.04MPa at 50°C and 0.12MPa at 90°C.

[0038] Preferably, in step (2), the leachate A is a mixed acid of HF, HCl and HNO3, wherein the concentration of HF is 1 mol / L to 6 mol / L, the concentration ratio of HCl to HNO3 is 3:1 to 12:1, the concentration ratio of (HCl+HNO3) to HF is ≤3, and the sum of the concentrations of HF, HCl and HNO3 is ≥3 mol / L. Regarding the ratio of leachate A, the inventors have experimentally found that the results of the test of the concentration ratio of hydrochloric acid to nitric acid in this range are better. Preliminary analysis shows that this is because HNO3 has strong oxidizing properties, while hydrochloric acid has complexing properties, which can further promote the reaction; the reason for limiting the concentration ratio of (HCl+HNO3) to HF to ≤3 is that the appropriate amount of H + It will promote the reaction, while too high a concentration of H+ It will inhibit the ionization of HF, resulting in a decrease in the purity of the high-purity quartz product; the sum of the concentrations of all acids is limited to ≥3 mol / L to avoid incomplete reaction due to the overall concentration being too low. In the leachate A, for example, the concentration of HF can be 1.5 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 5.5 mol / L, etc.; for example, the concentration ratio of HCl and HNO3 can be 12:1, 11:1, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, etc.; for example, the concentration ratio of (HCl+HNO3) and HF can be 0.25, 0.5, 1, 2, 3, etc.

[0039] Preferably, in step (2), the leaching temperature is 50°C to 160°C, a closed micro-pressure is used, the pressure increases with the temperature, the leaching time is ≥4h, and the liquid-solid ratio (the liquid-solid ratio in this article refers to the weight ratio) is 1:1 to 3:1. For example, the leaching temperature can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 155°C, 160°C; for example, the leaching time can be 4.5h, 6h, 8h, 10h, etc.; for example, the liquid-solid ratio can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, etc.

[0040] Preferably, in step (2), washing is first repeated 5 to 10 times with high-purity water (conductivity <0.1 μs / cm) until the pH is neutral, and then ultrasonic washing is performed 2 to 3 times with ethanol solution to remove organic matter remaining on the surface of quartz; more preferably, in ultrasonic washing, the ultrasonic power is 1000W to 1200W, the mass concentration of the ethanol solution is 10-30%, the liquid-solid ratio is ≥1, and the liquid-solid ratio is further preferably 10:1 to 3:1. For example, the ultrasonic power can be 1000W, 1050W, 1100W, 1150W, 1200W, etc.; for example, the concentration of the ethanol solution can be 10%, 15%, 20%, 25%, 30%, etc., and the liquid-solid ratio can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., and the liquid-solid ratio is further preferably 10:1 to 3:1. In the present application, ethanol cleaning is also used in step (2) to more thoroughly remove organic matter such as mineral processing agents remaining on the quartz surface, thereby better ensuring the quality of the subsequently prepared product without large bubbles.

[0041] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, in step (3), primary quartz sand is subjected to chlorination roasting in a tubular furnace, and then immediately water quenched, and centrifuged and dehydrated to obtain intermediate quartz sand.

[0042] Preferably, in step (3), the roasting temperature is 600°C to 1150°C, the roasting gas is Cl2 and / or HCl, and the roasting time is ≥ 6h. For example, the roasting temperature can be 650°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, etc.; the roasting gas can be Cl2, HCl, or a mixed gas of Cl2 and HCl; the roasting time can be 6.5h, 8h, 10h, 12h, etc.

[0043] Preferably, in step (3), the water quenching is performed by using high-purity water at room temperature.

[0044] In the above method for directional removal of impurity elements in pegmatite-type high-purity quartz, in step (4), the intermediate quartz sand is added to the leaching solution B, ultrasonic leaching is performed, and then it is repeatedly washed with high-purity water until the pH is neutral, centrifuged and dehydrated, and then subjected to high-temperature heat treatment to finally obtain high-purity quartz sand.

[0045] Preferably, in step (4), the leachate B is a mixed acid of HF and HCl, wherein the concentration of HF is 0.5 to 2 mol / L, and the concentration ratio of HCl to HF is ≤ 3. For example, the concentration of HF may be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, etc.; for example, the concentration ratio of HCl to HF may be 0.25, 0.5, 1, 2, 3, etc.

[0046] Preferably, in step (4), the ultrasonic time is 1h to 3h, the ultrasonic temperature is room temperature, the ultrasonic power is 1000W to 1200W, and the liquid-solid ratio is 1:1 to 5:1. For example, the ultrasonic time can be 1.5h, 2h, 2.5h, etc., the ultrasonic power can be 1000W, 1050W, 1100W, 1150W, 1200W, etc.; for example, the liquid-solid ratio can be 1.5:1, 2:1, 3:1, 4:1, 4.5:1, etc.

[0047] Preferably, in step (4), the high temperature heat treatment temperature is 1100°C to 1200°C, and the time is 0.5h to 5h. For example, the high temperature heat treatment temperature can be 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, etc., and the time can be 0.5min, 1h, 2h, 3h, 4h, 5h, etc. High temperature heat treatment will affect the performance of the crucible prepared from the high purity quartz product. If the high temperature heat treatment is not properly performed, the hydroxyl content is high, the crucible is difficult to form, or bubbles and bubble groups are easily formed.

[0048] The content of the present invention will be further described in detail by examples below, and the protection scope of the present invention includes but is not limited to the following examples. If no specific experimental steps or conditions are specified in the examples, the operations or conditions of the conventional steps described in the literature in the art can be carried out. The various reagents and raw materials used in the examples are all commercially available products unless otherwise specified.

[0049] The quartz raw material used in the embodiments and comparative examples of the present invention is of pegmatite type, and its main minerals are quartz (about 28%), plagioclase (about 62%), muscovite (about 8%) and a small amount of garnet (about 2%), and does not contain other dark minerals.

[0050] Examples 1-12 and Comparative Examples 1-9

[0051] A method for directional removal of impurity elements in pegmatite-type high-purity quartz, the process flow of which is shown in Figure 1 , including the following steps:

[0052] (1) After the pegmatite-type high-purity quartz raw material is crushed by a crusher, it is washed to remove surface impurities; then it is ground and classified to obtain a quartz sand raw material of -60 mesh to +180 mesh (i.e., 180 mesh above the sieve and 60 mesh below the sieve), and then the quartz sand raw material is re-selected in turn to remove heavy minerals and light minerals, and flotation is performed to remove monomer-dissociated feldspar and mica to obtain quartz concentrate;

[0053] (2) adding the quartz concentrate obtained in step (1) into the leaching solution A, performing constant temperature micro-pressure leaching in a closed container under leaching temperature conditions, then repeatedly washing with high-purity water (conductivity between <0.1 μs / cm) until the pH is neutral, then performing ultrasonic washing with ethanol to remove organic matter remaining on the surface of the quartz, and obtaining primary quartz sand after centrifugal dehydration; wherein the leaching solution A is a mixed acid of HF, HCl and HNO3, wherein the concentration of HF is 1 mol / L to 6 mol / L , the concentration ratio of HCl and HNO3 is 3:1 to 12:1, the ratio of the sum of the concentrations of HCl+HNO3 and HF is ≤3, and the sum of the concentrations of HF, HCl and HNO3 is ≥3 mol / L; the leaching temperature varies from 50°C to 160°C, a closed micro-pressure is used, the pressure increases with the increase of temperature, the leaching time is ≥4h, and the liquid-solid ratio is 1:1 to 3:1; the ultrasonic washing is specifically carried out 3 times with an ethanol solution of 10% by mass, the liquid-solid ratio is 1, and the ultrasonic power is 1200W;

[0054] (3) subjecting the primary quartz sand obtained in step (2) to chlorination roasting in a tubular furnace, and then immediately quenching with high-purity water at room temperature, and obtaining intermediate quartz sand after centrifugal dehydration; wherein the roasting temperature is 600° C. to 1150° C., the roasting gas is Cl2, HCl or a mixture of Cl2 and HCl, and the roasting time is ≥ 6 h;

[0055] (4) adding the intermediate quartz sand obtained in step (3) to the leachate B, performing ultrasonic leaching, and then repeatedly washing with high-purity water until the pH is neutral, centrifugally dehydrating and performing high-temperature heat treatment to finally obtain high-purity quartz sand; wherein the leachate B is a mixed acid of HF and HCl, wherein the concentration of HF is 0.5 to 2 mol / L, and the concentration ratio of HCl to HF is ≤3; the ultrasonic leaching time is 1 h to 3 h, the ultrasonic leaching temperature is room temperature, the ultrasonic power is 1200 W, and the liquid-solid ratio is 2:1 to 4:1; the high-temperature heat treatment temperature is 1150° C. and the time is 30 min.

[0056] The comparative examples have some changes in individual steps and process conditions based on the examples. For ease of understanding, the experimental conditions for directional removal of impurity elements from pegmatite-type high-purity quartz in the examples and comparative examples of the present application are summarized in Table 1 below.

[0057] Table 1 Summary of implementation conditions for directional removal of impurity elements in pegmatite-type high-purity quartz in various embodiments and comparative examples of this application

[0058]

[0059]

[0060]

[0061] The quartz concentrate obtained without calcination treatment in step (1) of Examples 1-12 and Comparative Examples 2-8 and

[0062] The content of the quartz concentrate obtained by calcination in step (1) of comparative example 1 (unit: μg / g) is as follows:

[0063] Table 2.

[0064] Table 2 Impurity element content in quartz concentrate prepared by different methods in this application (μg / g)

[0065] sample Al Ca Fe K Mg Na Ti B Cu Li Mn Ni P total Uncalcined 102.00 26.25 22.97 11.38 4.15 42.87 3.34 0.49 0.12 0.14 0.61 0.00 12.23 226.54 Calcination 121.32 46.23 42.93 51.23 6.18 96.23 3.45 0.51 0.15 0.15 0.77 0.00 13.25 382.40

[0066] The high-purity quartz sand obtained in the examples and comparative examples was tested.

[0067] The precise content of each impurity element in the sand. The impurity elements of the high-purity quartz prepared in the examples and comparative examples of this application

[0068] (Unit: μg / g) and quartz content (wt%) and yield are shown in Table 3.

[0069] Table 3 Impurity elements and quartz content (μg / g) and yield of high-purity quartz obtained in various examples and comparative examples of this application

[0070]

[0071] As can be seen from Table 3, Examples 1 to 12 and Comparative Examples 2 and 8 can prepare 4N8 grade high-purity quartz sand, but the high-purity quartz yields of Examples 1 to 12 are all above 80%, while the yields of Comparative Examples 2 and 8 are relatively low. The HF concentration in the leaching solution A of Comparative Example 2 is 10 mol / L, resulting in a sharp decrease in the yield at this stage, and the HF concentration in the leaching solution B of Comparative Example 8 is 4 mol / L, resulting in a decrease in the yield at this stage. Compared with the embodiments, Comparative Examples 2 and 8 have no significant improvement in product purity except for a decrease in yield.

[0072] In Comparative Example 1, a calcination-water quenching process was added between crushing and grinding according to conventional processes. In this stage, the impurity content was high, resulting in the impurity elements entering the lattice or lattice gap under high temperature conditions, which increased the difficulty of subsequent processing and made it difficult to remove some impurity elements.

[0073] Since HF is a weak acid, the dimer (HF)2 and HF2 - It will produce nucleophilic corrosion on Si atoms, break the Me-O bond, produce dissolution and promote the leaching of impurity elements. + Inhibits HF2 - The formation of HF leads to the weakening of the dissolution effect and incomplete leaching of impurity elements. In Comparative Example 4, the HF concentration was reduced in the leaching solution A. Since HF is a weak acid, when HF does not reach a certain concentration, the content of (HF)2 is low, resulting in the weakening of the dissolution effect and the reduction of the impurity removal rate. Comparative Examples 3 and 4 both lead to the reduction of Ca 2+ The impurity content is high, which affects the preparation of subsequent products.

[0074] After high temperature-water quenching, a large number of cracks and pits are generated on the surface of the quartz particles, exposing the inclusions and interstitial metal impurities, thereby increasing the chance of impurities contacting the acid and improving the impurity removal rate. Comparative Example 6 did not implement the chlorination roasting treatment in step (3), resulting in some inclusions not bursting, reducing the impurity removal rate. In Comparative Example 5, only calcination-water quenching was performed in step (3), and no gas was used (i.e., chlorination roasting was not used), which reduced the removal effect of impurity elements such as K and Na. The chlorination roasting in the present invention can chlorinate some metal oxides such as K and Na with chlorine gas, effectively reducing the impurity content. Not using chlorination roasting, only using calcination and water quenching process will reduce the removal rate of alkali metals such as potassium and sodium. In Comparative Example 7, the chlorination roasting temperature in step (3) is 500°C, which does not reach the removal temperature of impurity elements such as K and Na, so the impurity removal effect is not good; in addition, no water quenching was performed and the quartz crystal transformation temperature was not reached, resulting in insufficient inclusion bursting and poor impurity removal effect.

[0075] The present invention provides a method for directional removal of impurity elements in pegmatite-type high-purity quartz. The SiO2 content of the prepared high-purity quartz sand reaches more than 99.998wt%, the impurity elements are small, the sum of the contents of thirteen impurity elements is ≤20.00μg / g, the sum of the contents of Li, Na, and K elements is ≤2.00μg / g, the Fe element content is ≤0.50μg / g, the B element content is ≤0.20μg / g, and the yield is more than 80%. Therefore, the method for directional removal of impurity elements in pegmatite-type high-purity quartz provided by the present invention has the advantages of simple process, high product purity and high yield, and lays a foundation for future industrial implementation.

[0076] It should be noted that, in the present invention, unless otherwise understood in conjunction with the full text, if there is a statement of "A and / or B", it should be interpreted as any one of the following three parallel situations: A; B; A and B. Regarding the gas used in chlorination roasting being Cl2 and / or HCl, it should be interpreted as any one of the following three parallel situations: Cl2; HCl; a mixture of Cl2 and HCl.

[0077] It should also be noted that, in the present invention, in addition to being understood otherwise in conjunction with the full text, if any, the relevant terms should be understood as follows. Relational terms such as first and second, etc. are only used to distinguish an entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the term "includes", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements that are not clearly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements limited by the sentence "comprising one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements.

[0078] Although the present invention has been disclosed above by the description of the specific embodiments of the present invention, it should be understood that those skilled in the art can design various modifications, improvements or equivalents of the present invention within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present invention.

Claims

1. A method for directional removal of impurity elements in pegmatite-type high-purity quartz, characterized in that: The following steps are involved: (1) After the pegmatite-type high-purity quartz raw material is crushed by a crusher, it is washed, ground and classified to obtain quartz sand raw material of a certain particle size, and then re-selected and flotated to obtain quartz concentrate; (2) adding the quartz concentrate to a leaching solution A for constant temperature micro-pressure leaching, and obtaining primary quartz sand after washing; the leaching solution A is a mixed acid of HF, HCl and HNO3, wherein the concentration of HF is 1 mol / L to 6 mol / L, the concentration ratio of HCl to HNO3 is 3:1 to 12:1, the concentration ratio of (HCl+HNO3) to HF is ≤3, and the sum of the concentrations of HF, HCl and HNO3 is ≥3 mol / L; (3) roasting and water quenching the primary quartz sand to obtain intermediate quartz sand; (4) adding the intermediate quartz sand into the leaching solution B for ultrasonic leaching, washing and then performing high-temperature heat treatment to finally obtain high-purity quartz sand; the leaching solution B is a mixed acid of HF and HCl, wherein the concentration of HF is 0.5 to 2 mol / L, and the concentration ratio of HCl to HF is ≤3.

2. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to claim 1, characterized in that: In step (1), the pegmatite-type high-purity quartz raw material is directly crushed without any high-temperature heat treatment before grinding.

3. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to claim 1 or 2, characterized in that: In step (1), grinding and classification are performed to obtain quartz sand raw material with a particle size of -60 mesh to +180 mesh.

4. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to any one of claims 1 to 3, characterized in that: In step (2), the leaching temperature is 50° C. to 160° C., the leaching time is ≥ 4 h, and the liquid-to-solid ratio is 1:1 to 3:

1.

5. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to any one of claims 1 to 4, characterized in that: In step (2), the washing comprises: firstly washing repeatedly with high-purity water until the pH value is neutral; and then ultrasonically washing with an ethanol solution.

6. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to claim 5, characterized in that: In step (2), in the ultrasonic washing, the ultrasonic power is 1000W to 1200W, the mass concentration of the ethanol solution is 10-30%, the liquid-to-solid ratio is ≥1, and the preferred liquid-to-solid ratio is 10:1 to 3:

1.

7. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to claim 6, characterized in that: In step (2), the washing comprises: first washing with high-purity water for 5 to 10 times, and then ultrasonically washing with ethanol solution for 2 to 3 times.

8. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to any one of claims 1 to 7, characterized in that: In step (3), the primary quartz sand is subjected to chlorination roasting in a tubular furnace, and then immediately water quenched, and centrifuged to obtain the intermediate quartz sand; preferably, the roasting temperature is 600°C to 1150°C, the roasting gas is Cl2 and / or HCl, and the roasting time is ≥6h; preferably, the water quenching is performed by using high-purity water at room temperature.

9. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to any one of claims 1 to 8, characterized in that: In step (4), the ultrasonic leaching time is 1 h to 3 h, the temperature is room temperature, the ultrasonic power is 1000 W to 1200 W, and the liquid-to-solid ratio is 1:1 to 5:

1.

10. The method for directional removal of impurity elements in pegmatite-type high-purity quartz according to any one of claims 1 to 9, characterized in that: In step (4), the temperature of the high temperature heat treatment is 1100°C to 1200°C, and the time is 0.5h to 5h.

Citation Information

Patent Citations

  • Deep purification method of high-purity quartz sand

    CN114506847A

  • Ultrasonic oscillation-electro-adsorption cleaning method and purification process for high-purity quartz sand

    CN115321544A

  • Preparation method of 4N-grade high-purity quartz sand

    CN115872407A

  • Method for preparing 4N7-grade high-purity quartz sand from muscovite type granite quartz

    CN116605883A

  • Method for preparing 4N8-grade high-purity quartz sand from pegmatite quartz

    CN117623320A

Cited By

  • High-purity quartz sand and short-process heat treatment processing technology thereof

    CN120288786A